Trust Building in Managing Strata Residence in Kuala Lumpur - Omar, Abdul Jalil; Md Ariffin, Khadijah; Masram, Haidaliza (Research in Management of Technology and Business, 2023)
Abstract: Malaysians have shifted toward high-rise living in recent years especially in Kuala Lumpur. As a result, there is an understanding that this type of development must be managed as effectively as possible. Previously, strata residential building management was always associated with subpar maintenance work. As the number of high-rise buildings increases, a professional stratified residential building manager is becoming increasingly important. The purpose of this study was to identify the problems encountered by strata residential building managers in Malaysia, as well as strategies for dealing with existing problems. This research was carried out through interviews with stratified residential building managers. The objective of this study is to learn about the problems that exist in the management of stratified residential building maintenance and strategies for dealing with those problems. Findings indicate that the main issues with strata residential building management is that residents failure to collect maintenance fees from residence. Furthermore, poor maintenance such as the frequency of building defects and late of repair reduce the trust from residence. Suggestions to overcome the trust deficit are through to hold meetings with residents to solve any problem arise. Furthermore, management should carry out more scheduled maintenance activities to avoid major damage to the building. This effort able to keep the building well maintain and in good condition and ensuring the well-being of the building's occupants.